Analysis of Understanding of DPR Members against Gender Mainstreaming in DPRD Medan - Yurisna Tanjung; Sahran Saputra (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
The aims of this study is to find out the understanding DPR members agains gender mainstreaming in DPRD Medan. This study uses a qualitative case study approach. After in-depth interviews with 5 Members of the DPRD Medan, the researcher can conclude that: 1. Members DPRD Medan do not yet understand the term gender mainstreaming in development. 2. Members DPRD Medan have not provided full support for the acceleration of the development of women's empowerment and child protection. These two things are seen from the lack of DPRD initiative rights in the drafting of a specific Regional Regulation on the Protection of Women and Children in the City of Medan. 3. Between the Legislature and the Executive does not have an understanding of the protection of women and children, the executive should propose a draft regulation on the protection of women and children to be endorsed as a regional regulation.